Bacteria in the airways of patients with cystic fibrosis are genetically capable of producing VOCs in breath. (16th December 2016) - Bos, Lieuwe D J; Meinardi, Simone; Blake, Donald; Whiteson, Katrine
Abstract: Breath contains hundreds of volatile organic compounds (VOCs), the composition of which is altered in a wide variety of diseases. Bacteria are implicated in the formation of VOCs, but the biochemical mechanisms that lead to the formation of breath VOCs remain largely hypothetical. We hypothesized that bacterial DNA fragments in sputum of CF patients could be sequenced to identify whether the bacteria present were capable of producing VOCs found in the breath of these patients. Breath from seven patients with cystic fibrosis was sampled and analyzed by gas-chromatography and mass-spectrometry. Sputum samples were also collected and microbial DNA was isolated. Metagenomic sequencing was performed and the DNA fragments were compared to a reference database with genes that are linked to the metabolism of acetaldehyde, ethanol and methanol in the KEGG database. Bacteria in the genera Escherichia, Lactococcus, Pseudomonas, Rothia and Streptococcus were found to have the genetic potential to produce acetaldehyde and ethanol. Only DNA sequences from Lactococcus were implicated in the formation of acetaldehyde from acetate through aldehyde dehydrogenase family 9 member A1 (K00149). Escherichia was found to be genetically capable of producing ethanol in all patients, whilst there was considerable heterogeneity between patients for the other genera. The ethanol concentration in breath positively correlated with the amount of Escherichia found in sputum (Spearman rho = 0.85, P = 0.015). Rothia showed the most versatile genetic potential for producing methanol. To conclude, bacterial DNA fragments in sputum of CF patients can be linked to enzymes implicated in the production of ethanol, acetaldehyde and methanol, which are VOCs that are predictive of respiratory tract colonization and/or infection. This supports that the lung microbiome can produce VOCs directly.